Rancangan Bangun Sistem Keamanan Pintu Menggunakan Voice Command Berbasis Internet Of Things (IOT) - Dea Ervina Maharani; Agung Wicaksono; Danny Kurnianto (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2024)
Indonesian National Police (POLRI), from January to April 2023 there were 20,043 cases of theft in empty houses. Traditionalphysical locks are vulnerable to robbery and difficult to control remotely, so a more effective solution is needed. This researchproposes a door security system that can be voice controlled and remotely operated using Wemos D1 microcontroller andIoT technology. The system is equipped with an infrared sensor to detect objects, a selenoid to open and close the door,and a buzzer as an alarm. Sensor data is sent in real-time through the Antares platform. The average delay for the unlockcommand is 8.256 seconds and lock 7.353 seconds with MIT App Inventor, while for voice command lock 7.886 secondsand unlock 4.848 seconds, successfully tested 15 times.